PERANAN E-COMMERCE DALAM UPAYA MENINGKATKAN VOLUME PENJUALAN MESIN CRUSHER MMD MINERAL SIZING PADA PT. SAPARILO CAYDO JAKARTA - Sinaga, Lazarus (JIK: Jurnal Ilmu Komputer, 2017)
Indonesia is a developing country and will face an era of competition. This causes Indonesia to be involved in the competition. Marketing is a comprehensive system of business activities designed to plan, price, promote and distribute goods that can satisfy the desires of good services to both current and potential customers. Marketing is all business activities related to the flow of goods and services transfers from producer to final consumer. E-commerce is a purchase, sale, marketing of services and goods through electronic or internet systems. E-commerce can involve the exchange of electronic data, electronic funds, as well as electronic inventory systems. Promotional activities carried out by PT Saparilo Caydo more focused on online transaction activities. E-commerce plays a key role in supporting the success of PT Saparilo Caydo in increasing the sales volume of crusher machine. E-commerce is a means of liaison between producers and prospective customers to make transactions easily anytime and anywhere.Ã‚Â Keywords: e-commerce, sales volume, pt. saparilo caydo